2012
DOI: 10.1016/j.clinbiochem.2011.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the determination of human acylated ghrelin plasma concentrations using a double antibody enzyme immunometric assay

Abstract: Hemolysis and AEBSF may affect AG determination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Trivedi and coworkers (36) showed that AEBSF may inhibit acetylcholinesterase (AChE) activity from the kits and thus may change AG levels. However, this problem of AEBSF suppressing AChE activity is circumvented using the applied processing method and Bertin Pharma EIA kits described by Delhanty and coworkers (3).…”
Section: Discussionmentioning
confidence: 99%
“…Trivedi and coworkers (36) showed that AEBSF may inhibit acetylcholinesterase (AChE) activity from the kits and thus may change AG levels. However, this problem of AEBSF suppressing AChE activity is circumvented using the applied processing method and Bertin Pharma EIA kits described by Delhanty and coworkers (3).…”
Section: Discussionmentioning
confidence: 99%
“…The assays differ in that the capture antibody in the Bertin Pharma ELISA plate will bind both forms of ghrelin, and it is the tracer (detection antibody) that provides specificity for the assay. The tracer is an AChE‐conjugated Fab, requiring a stringent wash step following sample incubation in the plate as AChE is inhibited by AEBSF . The SCETI assay is essentially the reverse, as it uses capture antibodies that are specific for each form of ghrelin with a common, nonspecific (for ghrelin), tracer (HRP‐conjugated) antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, it is customary when preparing plasma for subsequent assay of acyl ghrelin to add a protease inhibitor such as PHMB (p-hydroxymercuribenzoate) prior to the HCl stabilization step as another step to stabilize the acyl group (26,35,58). To test the requirement for the protease inhibitor with the current cell culturebased system, pilot secretion studies were performed as described above in serum-free DMEM medium (containing penicillin, streptomycin, and octanoate-BSA) plus 1, 5, or 10 mM D-glucose (as described above) with or without 0.05% DMSO.…”
Section: Methodsmentioning
confidence: 99%